Oxidation of a non-phenolic lignin model compound by two Irpex lacteus manganese peroxidases: evidence for implication of carboxylate and radicals - Qin, Xing (Biotechnol Biofuels, 2017)
BACKGROUND: Manganese peroxidase is one of the Class II fungal peroxidases that are able to oxidize the low redox potential phenolic lignin compounds. For high redox potential non-phenolic lignin degradation, mediators such as GSH and unsaturated fatty acids are required in the reaction. However, it is not known whether carboxylic acids are a mediator for non-phenolic lignin degradation. RESULTS: The white rot fungus Irpex lacteus is one of the most potent fungi in degradation of lignocellulose and xenobiotics. Two manganese peroxidases (IlMnP1 and IlMnP2) from I. lacteus CD2 were over-expressed in Escherichia coli and successfully refolded from inclusion bodies. Both IlMnP1 and IlMnP2 oxidized the phenolic compounds efficiently. Surprisingly, they could degrade veratryl alcohol, a non-phenolic lignin compound, in a Mn(2+)-dependent fashion. Malonate or oxalate was found to be also essential in this degradation. The oxidation of non-phenolic lignin was further confirmed by analysis of the reaction products using LC–MS/MS. We proved that Mn(2+) and a certain carboxylate are indispensable in oxidation and that the radicals generated under this condition, specifically superoxide radical, are at least partially involved in lignin oxidative degradation. IlMnP1 and IlMnP2 can also efficiently decolorize dyes with different structures. CONCLUSIONS: We provide evidence that a carboxylic acid may mediate oxidation of non-phenolic lignin through the action of radicals. MnPs, but not LiP, VP, or DyP, are predominant peroxidases secreted by some white rot fungi such as I. lacteus and the selective lignocellulose degrader Ceriporiopsis subvermispora. Our finding will help understand how these fungi can utilize MnPs and an excreted organic acid, which is usually a normal metabolite, to efficiently degrade the non-phenolic lignin. The unique properties of IlMnP1 and IlMnP2 make them good candidates for exploring molecular mechanisms underlying non-phenolic lignin compounds oxidation by MnPs and for applications in lignocellulose degradation and environmental remediation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13068-017-0787-z) contains supplementary material, which is available to authorized users.